Aerial reconfigurable intelligent surface assisted vehicle-to-vehicle communication - Chee, Yen Leow; Hashim, Norlezah; Moessner, Klaus; Chuan, Heng Foh (Institute Of Electrical And Electronics Engineers Inc., 2025)
Vehicle-to-vehicle (V2V) communication enhances safety by allowing moving vehicles to exchange real-time information. However, due to dynamic environments, V2V links are vulnerable to blockage due to obstacles. We propose the use of aerial reconfigurable intelligent surface (ARIS) mounted on an unmanned aerial vehicle (UAV) to enhance V2V communication reliability by reflecting the signal between moving vehicles. Then we adopt the power consumption models for multirotor UAVs, where three flight statuses, i.e., forward flight, vertical ascent, and vertical descent, are included into the system model. The optimization problem is formulated to maximize energy efficiency (EE) by jointly optimizing the three-dimensional (3D) position of ARIS and the transmit power of the system, while ensuring a minimum data rate requirement to meet quality-of-service (QoS) constraints. Due to the non-convexity of the formulated problem, the EE optimization is solved using Dinkelbach’s iterative algorithm and interior point method. Simulation results demonstrate that the proposed scheme outperforms benchmark methods, with optimized hybrid ARIS yielding the highest EE compared to passive ARIS scheme.